Analisis Hukum terhadap Kasus Penyalahgunaan Fungsi Perbankan: Studi Kasus dan Implikasinya bagi Perlindungan Konsumen di Indonesia - Wiwin Muchtar Wiyono; Aris Priyadi; Ferryani Krisnawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the forms of banking abuse, examine the legal accountability of perpetrators of banking abuse, and analyze its implications for consumer protection in Indonesia. The study uses a normative legal research method with a statute approach, a conceptual approach, and a case approach. The legal materials used consist of primary, secondary, and tertiary legal materials obtained through literature studies, then analyzed qualitatively using normative juridical analysis methods. The results of the study indicate that banking abuse generally occurs in the form of misuse of customer funds, misuse of personal data, violations of the prudential banking principle, abuse of authority by bank officials, and the provision of non-transparent information to consumers. Although Indonesia has various legal instruments regulating consumer protection in the banking sector, the implementation of legal protection still faces obstacles such as weak internal supervision, low legal and financial literacy among the public, and the increasing complexity of digital banking services. Therefore, it is necessary to strengthen the implementation of the prudential principle, good corporate governance, supervision by the Financial Services Authority (OJK), and improve the effectiveness of dispute resolution mechanisms to provide optimal legal protection to banking consumers.